Evaluation of diaphragm in patients with chronic obstructive pulmonary disease using ultrasonography in relation to disease severity in Fayoum University Hospital - Sherif R Abd El-Fattah; Radwa A El Hefny; Yosra S Fathy; Enas S Farhat (Egyptian Journal of Chest Disease and Tuberculosis, 2023)
Background Diaphragmatic evaluation is crucial in the diagnosis of patients with chronic obstructive pulmonary disease (COPD). Diaphragmatic ultrasound is a simple, noninvasive, and bedside method. Ultrasound can analyze the diaphragm’s location, structure, and motility, as well as excursion and thickness.The study’s goal is to assess the diaphragm by ultrasonography in patients with COPD and relationship to disease severity. During their follow-up at the outpatient chest clinic, 40 patients with stable COPD and 40 healthy controls were studied for a year. Results The diaphragmatic measurements (thickening at total lung capacity and residual volume, excursion, and diaphragm thickness percentage) detected by ultrasonography were observed to decrease with increasing COPD severity.Furthermore, in comparison with the control group, these parameters were shown to be considerably lower in patients with COPD. Conclusion Ultrasonography is a safe, noninvasive, and straightforward approach for determining diaphragmatic thickness and excursion.The thickness and excursion of the diaphragmatic function were found to have a negative relationship with COPD severity.